ChemInform Abstract: Direct Diphosphonylation of Quinolines with H‐Phosphonates under Metal‐Free Conditions. Issue 50 (December 2015) - Zhang, Qianqian; Wei, Donghui; Cui, Xiuling; Zhang, Duo; Wang, Hui; Wu, Yangjie
Abstract: Electronic effects have no significant influence on the reaction while steric effects reduce yields remarkably.